2021
DOI: 10.3390/biom11020157
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-193a-5p Regulates the Synthesis of Polyunsaturated Fatty Acids by Targeting Fatty Acid Desaturase 1 (FADS1) in Bovine Mammary Epithelial Cells

Abstract: Cardiovascular diseases (CVDs) are seriously threatening to human life and health. Polyunsaturated fatty acids (PUFAs) are known for their role in preventing CVDs. It is beneficial to population health to promote the content of PUFAs in bovine milk. In recent years, limited research based on molecular mechanisms has focused on this field. The biological roles of numerous microRNAs (miRNAs) remain unknown. In this study, a promising and negatively correlated pair of the miRNA (miRNA-193a-5p) and a fatty acid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Recently, the ability of miR-485 to regulate the synthesis of triglycerides, non-esterified fatty acids, and cholesterol in the mammary epithelial cells of cows, by inhibiting the expression of the DTX4 gene, which is a PPAR-γ transcription factor, was observed [141]. Additionally, recently demonstrated the regulation of the synthesis of polyunsaturated fatty acids by miR-193a-5p through the modulation of fatty acid desaturase 1 (FADS1), leading the authors to conclude a role for this miRNA in regulating the amount of milk fatty acids in the epithelial cells of the mammary glands of cattle [142].…”
Section: Lipid Metabolismmentioning
confidence: 95%
“…Recently, the ability of miR-485 to regulate the synthesis of triglycerides, non-esterified fatty acids, and cholesterol in the mammary epithelial cells of cows, by inhibiting the expression of the DTX4 gene, which is a PPAR-γ transcription factor, was observed [141]. Additionally, recently demonstrated the regulation of the synthesis of polyunsaturated fatty acids by miR-193a-5p through the modulation of fatty acid desaturase 1 (FADS1), leading the authors to conclude a role for this miRNA in regulating the amount of milk fatty acids in the epithelial cells of the mammary glands of cattle [142].…”
Section: Lipid Metabolismmentioning
confidence: 95%
“…Overall, studies on the roles of miRNA in the regulation of LC-PUFA biosynthesis have only been reported in S. canaliculatus, but not yet in other fish species or other vertebrates, except for miR-193a-5p that was shown to regulate LC-PUFA biosynthesis by targeting FADS1 in bovine mammary epithelial cells [172]. As described above, individual miRNA or clusters regulated rabbitfish LC-PUFA biosynthesis by targeting fads2, elovl or TF-encoding genes.…”
Section: Role Of Mirna Clusters In the Regulation Of Lc-pufa Biosynth...mentioning
confidence: 99%
“…The miR-204-5p and miR-211 were found to coordinately inhibit the content of α-S1 casein (CSN1S1) (4). The effect of other miRNAs on MECs has also been reported, including miR-193a-5p (5), miR-128 (6), miR-106b (7), miR-221 (8), miR-16a (9), and miR-26a/b (10). However, these studies have been focused on dairy cows and dairy goats.…”
Section: Introductionmentioning
confidence: 95%